PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, SISTEM PENGENDALIAN INTERN, MORALITAS DAN WHISTLEBLOWING TERHADAP PENCEGAHAN KECURANGAN (FRAUD) PENGELOLAAN DANA DESA (STUDI EMPIRIS PADA DESA SE-KECAMATAN PAYANGAN) - Ni Kadek Ayu Suandewi (Hita Akuntansi dan Keuangan, 2021)
Fraud prevention is an effort or action taken to minimize opportunities, ward off and assess any activity that has the risk of fraud. This study aims to determine the effect of human resource competence, internal control systems, morality and whistleblowing on the prevention of fraud in village fund management in Payangan Subdistrict Villages. The population in this study were all village officials in Payangan District. The sample in this study was determined with the help of the Slovin formula with a total of 59 village officials. The sampling method used was proportionate stratified random sampling. From the results of this study, human resource competence has a positive and significant effect on fraud prevention, the internal control system has no effect on fraud prevention, morality has no effect on fraud prevention, and whistleblowing has a positive and significant effect on fraud prevention.